Analysis on Delta-Vs to Maintain Extremely Low Altitude on the Moon and Its Application to CubeSat Mission - Young-Joo Song; Donghun Lee; Young-Rok Kim (Journal of Astronomy and Space Sciences, 2019)
This paper analyzes delta-Vs to maintain an extremely low altitude on the Moon and investigates the possibilities of performing a CubeSat mission. To formulate the station-keeping (SK) problem at an extremely low altitude, current work has utilized real-flight performance proven software, the Systems Tool Kit Astrogator by Analytical Graphics Inc. With a high-fidelity force model, properties of SK maneuver delta-Vs to maintain an extremely low altitude are successfully derived with respect to different sets of reference orbits; of different altitudes as well as deadband limits. The effect of the degree and order selection of lunar gravitational harmonics on the overall SK maneuver strategy is also analyzed. Based on the derived SK maneuver delta-V costs, the possibilities of performing a CubeSat mission are analyzed with the expected mission lifetime by applying the current flight-proven miniaturized propulsion system performances. Moreover, the lunar surface coverage as well as the orbital characteristics of a candidate reference orbit are discussed. As a result, it is concluded that an approximately 15-kg class CubeSat could maintain an orbit (30–50 km reference altitude having ±10 km deadband limits) around the Moon for 1–6 months and provide almost full coverage of the lunar surface.